Based on UPLC-Q-TOF/MS and Network Pharmacology to Explore the Mechanism of Qingre Lishi Decoction in the Treatment of Psoriasis - Wei J; Liu Z; Li M; Du L; Zhu X; Leng Y; Han C; Xu Q; Zhang C (Dove Medical Press, 2024)
Jingjing Wei,1,* Zhaoyang Liu,1,2,* Mingming Li,1 Lingyun Du,1 Xia Zhu,1 Yi Leng,1 Changyu Han,1 Qingqing Xu,1 Chunhong Zhang1 1Department of Dermato-Venereology, the Second Hospital, Cheeloo College of Medicine, Shandong University, Jinan, People's Republic of China; 2Department of Dermato-Venereology, Tianjin Medical University General Hospital, Tianjin, People's Republic of China*These authors contributed equally to this workCorrespondence: Chunhong Zhang, Department of Dermato-Venereology, the Second Hospital, Cheeloo College of Medicine, Shandong University, 247 Beiyuan Dajie Street, Jinan, People's Republic of China, Tel +86-531-85875027, Fax +86-531-88962544, Email aliu133@163.comBackground: Psoriasis is an immune-mediated chronic inflammatory disease. Qingre Lishi Decoction (QRLSD) has achieved great clinical effect in the treatment of psoriasis. However, the potential bioactive components and the mechanisms are yet unclear.Aim: To analyze the serum parameters of rats fed with QRLSD, screen out the active components of QRLSD, and explore the potential targets and pathway of QRLSD in the treatment of psoriasis.Materials and Methods: The active components of serum containing QRLSD were analyzed using ultra-high performance liquid chromatography quadrupole-time-of-flight mass spectrometry (UPLC-Q-TOF/MS). The targets of QRLSD in the treatment of psoriasis were predicted by network pharmacology and molecular docking. In vitro experiments verified the underlying mechanism.Results: By UPLC-Q-TOF/MS, 15 prototype components and 22 metabolites were identified in serum containing QRLSD. Subsequently, 260 chemical composition targets and 218 psoriasis targets were overlapped to obtain 23 intersection targets, including LGALS3, TNF, F10, DPP4, EGFR, MAPK14, STAT3 and others. TNF, IL-10, GAPDH, STAT3, EGFR, ITGB1, LGALS3 genes were identified as potential drug targets in the PPI network analyzed by CytoHubba. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses indicated that QRLSD may improve psoriasis by regulating immune and inflammatory pathways, the cytokine mediated signal transduction pathways and other signaling pathways. Molecular docking results showed that the main active components of the serum containing QRLSD had higher affinities for TNF and LGALS3. In vitro experiments confirmed that QRLSD may decrease levels of inflammatory cytokines by suppressing the NF-κB signaling pathway activated by TNF-α in human keratinocytes.Conclusion: This study explores the potential compounds, targets and signaling pathways of QRLSD in the treatment of psoriasis, which will help clarify the efficacy and mechanism of QRLSD.Keywords: qingre lishi decoction, psoriasis, UPLC-Q-TOF/MS, network pharmacology, molecular docking, NF-κB signaling pathway